The Midwifery Model of Care: A Quality Maternal and Newborn Health Initiative - Neupane, Sharmila (Journal of Nursing Education of Nepal, 2023)
The Midwifery model of care is based on the evidences that most pregnancies, labors, and births are  normal biological processes that result in healthy outcomes for both mothers and babies. It consists  of maximizing the health and wellbeing of mother and baby, early identification and management  of health problems including emotional, social and spiritual aspects of pregnancy and birth. The  Midwifery model of care include; monitoring physical, psychological and social well-being of the  mother; providing individualized continuity of care, education, counseling and hands-on assistance;  minimizing technological intervention and identifying and referring women who require obstetrical  attention. Evidences from Sweden, UK and Malaysia have shown that midwifery model is associated  with a number of important benefits for mothers and babies. Most studies reported greater satisfaction  with midwifery-led model of care compared with other models and it is cheaper and women friendly.  The history of midwife led center in Patan Hospital, other hospitals are the milestone in Nepal, and  recent government initiation of onsite midwife led birthing unit (OMBU) is remarkable.  All pregnant women should be offered midwifery model of care unless they have serious  medical or obstetric complications requiring medical attention and government initiatives for OMBU  and professional midwives are our road map for quality care.
Keywords: Continuity of care; Midwife; Midwifery model